Green Building Concept of Residential Housing in Lebanon - Fawal, Hani El (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
Recent years has seen a gradual increase of interest in green buildings due to their many advantages and positive effect on the environment, economy and our lifestyle. Hence, for achieving more benefits from green buildings, there is more research into this subject in order to further improve this concept. In addition to incentives provided for building green in developed countries like United States and United Kingdom, with the support of non-government organizations assessments based on green certification programs, such as, BREEAM and LEED has been established. On the other hand, countries like Lebanon are still unable to implement green buildings in an efficient manner. The purpose of this study is to discuss the importance of green building concepts for residential buildings and investigate the situation in Lebanon. For this reason, a survey was conducted targeting the Lebanese general public and professionals for better understanding of their knowledge and awareness regarding green buildings. The residential building Factory 4376 is located near the Lebanese capital city of Beirut. It is the case study that was evaluated by using the BREEAM certification categories and as a result it was promoted to BREEAM "GOOD" classification, ranging from 45% to 55%. The survey results are presented through which the problems affecting the development of green buildings in Lebanon are identified. Thus, it is expected that this study will contribute towards understanding matters relating to sustainable development in general and green residential buildings in particular. Keywords: green building in Lebanon, BREEAM, LEED, green products, Lebanese market.

Öz: Son yıllarda bu binaların çevre, ekonomi ve yaşam tarzımıza etki eden birçok avantaj ve pozitif etkilerinden dolayı yeşil binalara karşı ilgi kademeli olarak artmıştır. Bundan dolayı, yeşil binalardan daha çok faydalanabilmek için bu konuyla ilgili kavramları daha çok geliştirme adına daha çok araştırmalar yapılmaktadır. Amerika Birleşik Devletleri ve İngiltere gibi gelişmiş ülkelerde devletin verdiği teşviklere ilaveten sivil toplum örgütlerinin desteğiyle BREEAM ve LEED gibi yeşil sertifika programları başlatılmıştır. Diğer yandan, Lübnan gibi ülkeler halen yeşil binaları etkin bir şekilde uygulayamamaktadırlar. Bu çalışmanın amacı meskun binalar için yeşil bina konseptinin önemini tartışmak ve Lubnan‟daki durumu araştırmaktır. Bu nedenle, Lubananlı genel halk ve profesyonellerin yeşil binalarla ilgili bilgi ve farkındalığını ölçeçek bir anket hazırlanmıştır. Meskun bina Factory 4376 Lubnan‟ın baş kenti Beyrut yakınlarındadır. Bu bina örnek olay olarak BREEAM serifika programı kullanılarak değerlendirilmiş ve %45 ile %55 arasında toplanılan puanlarla BREEAM „İYİ‟ sınıflandırması almıştır. Anket sonuçları kullanılarak Lubnan‟da yeşil bina konseptini etkileyen problemler tespit edildi. Böylece, bu çalışmanın genelde sürdürülebilir kalkınma ve özelde de yeşil meskun binaların daha iyi anlaşılması için katkı koyması beklenmektedir. Anahtar Kelimeler: Lubnan‟da yeşil bina, BREEAM, LEED, yeşil ürünler, Lübnan pazarı.
Master of Science in Civil Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2015. Supervisor: Assist. Prof. Dr. Mürüde Çelikağ.
Keywords: Civil Engineering; Green Building; Lebanon; Sustainable buildings; Construction; Lebanon; Ecological houses; Design and construction; Renewable energy sources; Economic aspects; Buildings; Architecture and energy conservation; Energy consumption; green building in Lebanon; BREEAM; LEED; green products; Lebanese market